Sistem Informasi Digitalisasi Laporan Kegiatan Pasukan Damkar Surakarta Berbasis Web - Humam Rosadi; Nibras Fa’id Muhammad; Sri Sumarlinda (Pusat Riset dan Inovasi Nasional, 2025)
The Surakarta Fire Department faces challenges in manually recording team activities, leading to delays in validation, data inconsistency, and difficulties in analysis. To address these issues, this study designed a web-based information system to digitize personnel activity reporting. The system was developed using the Rapid Application Development (RAD) method with the Laravel framework and MySQL database. Data collection methods included interviews, observation, and literature study. The system supports four levels of users with different access rights: Personnel, Team Leader, Platoon Commander, and Division Head. Through this system, reporting can be conducted online with step-by-step validation and PDF report output. Initial testing showed that the system successfully accelerated the reporting process, reduced data errors, improved efficiency, and supported decision-making within the Surakarta Fire Department.